dBcAMP Rescues the Neurons From Degeneration in Kainic Acid-Injured Hippocampus, Enhances Neurogenesis, Learning, and Memory - Rao, Muddanna Sakkattu; Abd-El-Basset, Ebtesam M. (Frontiers in Behavioral Neuroscience, 2020)
Abstract: Dibutyryl cyclic adenosine monophosphate (dBcAMP) is a cell-permeable synthetic analog of cyclic adenosine monophosphate (cAMP). Although elevation of cAMP levels was reported to promote the functional recovery in spinal cord injury, its role in neurogenesis, functional recovery in hippocampal injury is unknown. The objective of the study was to investigate the effects of dBcAMP on learning, memory and neurogenesis in excitotoxically lesioned hippocampus. An excitotoxic lesion was induced in the hippocampi of four months old male BALB/c mice by injecting 0.25µg/ µl into the lateral ventricles of both sides. Lesioned mice (L) were divided into L+ dBcAMP and L+PBS groups. Sham surgery was done (S), by injection of 1µl of sterile saline into the lateral ventricles. The sham surgery mice were divided into S+dBcAMP and S+PBS groups. Mice in L+dBcAMP and S+dBcAMP groups were treated with dBcAMP for one-week (ip,50mg/kg/day) whereas, mice in L+PBS and S+PBS groups were treated with PBS. Mice in all groups were subjected to water maze and passive avoidance tests at the end of 4th week. Cresyl violet staining, NeuN and DCX immunostaining were done to analyze the morphology and neurogenesis. Water maze learning sessions, showed significantly better learning performance in L+dBcAMP mice. Memory retention test showed that L+dBcAMP mice had significantly short entry latency and higher target quadrant time/distance traveled compared to L+PBS group suggesting better memory retention. Passive avoidance test showed that L+dBcAMP had significantly improved memory retention compared to L+PBS mice. Morphological studies showed significantly more number of adult neurons and increased neurogenesis in the hippocampus in L+dBcAMP compared to L+PBS group. There was no significant difference between S+dBcAMP and S+PBS groups in water maze/passive avoidance tests and number of neurons. In conclusion, dBcAMP protects the hippocampal neuron from degeneration and enhances neurogenesis, learning and memory.